Pengaruh Kualitas Pelayanan Bank BTN Terhadap Kepuasan Nasabah Dengan Physical Evidence Sebagai Variabel Moderating (Studi Kasus Pada KPM PKH di Kecamatan Koroncong Kabupaten Pandeglang Provinsi Banten) - Hayati, Hayati (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2020)
The aims of study were to analyze the effect of BTN Bank service quality on customer satisfaction on KPM PKH in Koroncong Sub-district, analyze the effect of physical evidence on customer satisfaction on KPM PKH in Koroncong Sub-district, and analyze the effect of service quality on customer satisfaction with physical evidence as moderating variable. Proportional sampling method is applied to obtain 95 respondents, then analyzed by SEM-PLS. The result showed that service quality and physical evidence have positive effect and significant on customer satisfaction, but physical evidence does not moderate the effect of service quality on customer satisfaction on KPM PKH in Koroncong Sub-district, Pandeglang Regency.